Effect of nutrition awareness on utilization of Orange Fleshed Sweetpotato among vulnerable populations in Kenya - Mulwa, C.K.; Heck, S.; Maru, J.; Mwema, J.; Campos, Hugo (Springer, 2023)
Malnutrition continues to affect many vulnerable populations worldwide, with the majority of these residing in developing and underdeveloped countries. This problem has been exacerbated by the changing climate and more recently by the COVID-19 pandemic. Urgent efforts geared towards enhancing sustainable production and value chains of nutritious foods to ensure access to healthier diets are therefore critical. A recent partnership between the World Food Programme and the International Potato Center to enhance utilization of biofortified crops in fragile environments in Kenya is a step in this direction, aimed at improving the diets of households at risk of hunger and malnutrition. This study sets out to provide early evidence on the potential impacts of the interventions spearheaded in this partnership, together with lessons for further scaling efforts. Using household level data, the study adopts an impact evaluation framework to understand the effect of nutrition awareness through the dissemination of information on Vitamin A deficiency, on the utilization of orange fleshed sweetpotato, a biofortified crop rich in Vitamin A. Results show positive and significant effects of nutrition awareness on utilization of the orange-fleshed sweetpotato. Several factors were also identified as key to determining the exposure to nutrition awareness, including proximity to markets and extension agents, gender, and education levels. For widespread and inclusive adoption and utilization of orange-fleshed sweetpotato, out-scaling efforts need to consider these determinants in designing interventions aimed at raising nutrition awareness, as a key entry point to enhancing utilization of orange-fleshed sweetpotato.